2021
DOI: 10.1155/2021/5129302
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Trio-Anthropometric Predictors of Hypertension: Determining the Susceptibility of Blood Pressure to Sexual Dimorphism in Body Stature

Abstract: Background. Several studies had suggested that complex body stature could be a risk factor of hypertension. Objectives. We aim to correlate body mass index (BMI), waist-hip ratio (WHR), and waist-height ratio (WHtR) of rural dwellers in Afikpo community, Ebonyi State, Nigeria, with blood pressure parameters. Furthermore, we aim to ascertain how each of the anthropometric variables affects blood pressure in men and women, respectively. Materials and Methods. A sample of 400 (200 males and 200 females) adults ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…41,42 A correlationbased analysis by Ezemagu et al showed how a significant increase in body mass index, waist circumference, and waist-to-height ratio could cause hypertension and variations in systolic blood pressure, diastolic blood pressure, and pulse pressure. 43 In another recent study by Osama et al it was discovered that in Egyptian patients, the probability of developing a more severe form of COVID-19 is increased by obesity and its associated comorbidities. 44 According to Chukwu et al adopting a healthier lifestyle will probably lead to a decrease in the population of obese and hypertensive people in the community.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 A correlationbased analysis by Ezemagu et al showed how a significant increase in body mass index, waist circumference, and waist-to-height ratio could cause hypertension and variations in systolic blood pressure, diastolic blood pressure, and pulse pressure. 43 In another recent study by Osama et al it was discovered that in Egyptian patients, the probability of developing a more severe form of COVID-19 is increased by obesity and its associated comorbidities. 44 According to Chukwu et al adopting a healthier lifestyle will probably lead to a decrease in the population of obese and hypertensive people in the community.…”
Section: Discussionmentioning
confidence: 99%
“…In our locality, 36% of women give birth at home with the help of relatives or a traditional birth attendant, which results to 35% mortality rate of neonates in Ebonyi State, which affects more male birth than female birth: Nigeria Demographic and Health Survey (20). Globally, out of four million deaths of neonates annually, 98% occur due to poverty, ignorance or lackadaisical attitude of mothers and birth attendants in developing countries (21). Following the cultural expectation and death rate of male children in our locality, efforts to improve the birth outcomes are highly required.…”
Section: Introductionmentioning
confidence: 99%